Experimental evaluation of the specific activity of the new Angiolin dosage form in the research corneal burn's condition - I. F. Bielenichev; L. I. Kucherenko; I. A. Mazur; R. R. Akopian; O. V. Khromylova; I. V. Pavliuk (Zaporožskij Medicinskij Žurnal)
Visual organ injuries are still one of the main causes of blindness and occupational disability. Despite the good protection of the eyeball by the bone walls of the orbit and adnexa oculi, its injuries are 5–10 % of the total number of all damages in peacetime and about 20 % in wartime.